Outcomes of allogeneic haematopoietic stem cell transplantation for paediatric patients with MLL-rearranged acute myeloid leukaemia - Lu Bai; Yong-zhan Zhang; Chen-hua Yan; Yu Wang; Lan-ping Xu; Xiao-hui Zhang; Le-ping Zhang; Xiao-jun Huang; Yi-fei Cheng (BMC Cancer, 2022)
Abstract Background The presence of mixed-lineage leukaemia rearrangement (MLL-r) in paediatric patients with acute myeloid leukaemia (AML) is a poor prognostic predictor. Whether allogeneic haematopoietic stem cell transplantation (allo-HSCT) is beneficial in such cases remains unclear. Methods We evaluated the outcomes and prognostic factors of allo-HSCT in 44 paediatric patients with MLL-r AML in the first complete remission (CR1) between 2014 and 2019 at our institution. Results For all the 44 patients, the 3-year overall survival (OS), event-free survival (EFS), and cumulative incidence of relapse (CIR) were 74.5%, 64.1%, and 29.1%, respectively. Among them, 37 (84.1%) patients received haploidentical (haplo)-HSCT, and the 3-year OS, EFS, and CIR were 73.0%, 65.6%, and 26.4%, respectively. The 100-day cumulative incidence of grade II–IV acute graft-versus-host disease (aGVHD) post-transplantation was 27.3%, and that of grade III–IV aGVHD was 15.9%. The overall 3-year cumulative incidence of chronic graft-versus-host disease (cGVHD) post-transplantation was 40.8%, and that of extensive cGVHD was 16.7%. Minimal residual disease (MRD)-positive (MRD +) status pre-HSCT was significantly associated with lower survival and higher risk of relapse. The 3-year OS, EFS, and CIR differed significantly between patients with MRD + pre-HSCT (n = 15; 48.5%, 34.3% and 59%) and those with MRD-pre-HSCT (n = 29; 89.7%, 81.4% and 11.7%). Pre-HSCT MRD + status was an independent risk factor in multivariate analysis. Conclusions Allo-HSCT (especially haplo-HSCT) can be a viable strategy in these patients, and pre-HSCT MRD status significantly affected the outcomes.